HUBUNGAN KOORDINASI MATA TANGAN, POWER LENGAN, KESEIMBANGAN BADAN BACKHAND DRIVE PETENIS PUTERA (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This study on the Relationship discuss to Eye Coordination Hand , Arm and Power Balance Board to Conduct Capability Driver for tennis male player backhand Club Tegal 2012. Research using research methods that directly spaciousness and data collection by performing test measurements . Data were analyzed using analysis and description of the percentage of the product moment correlation analysis .The results of each of the variables showed that : 1 ) . Median value test hand -eye coordination is at 7.80 . and categorized Well , 2 .) average power arm strength test value is equal to 7.86 and categorized Good, 3 ) . grade average test weight balance is at 7.77 and categorized as Good, 4 ) . median end eye coordination test scores hands , arms and body balance power is 7.83 and categorized Neither 5 ) . The average capacity is 2 tennis backhand drive letter ( 6.6 % ) both capable all, 14 players ( 46.7 % ) and the rest is well -capable players ( 46.7 % ) have the ability to drive a pretty backhand . The end result of this research is the acceptance of the proposed hypothesis because slanting between hand -eye coordination , arm power and the ability to balance the body for male tennis backhand drive club Tegal in 2012 there is a significant relationship either at the level of 5 % and 1 %.